Effect of the fluidic injection on the flow of a converging-diverging conical nozzle - Benderradji, Razik; Gouidmi, Hamza; Beghidja, Abdelhadi Abdelhadi (جامعة الوادي - university of el oued, 2020)
The flow in an Over-Expanded Nozzle is subjected to shock waves leading to the unsteady separation of the boundary layer. Free detachment may be followed by a restricted detachment. During the expansion regime in propellant nozzles, several physical phenomena are encountered: supersonic jet, jet separation, adverse pressure gradient, shock wave, turbulent boundary layer, highly compressible mixture layer, return flow, large scale turbulence. These very complex phenomena can considerably affect the performance of the nozzle.The numerical investigation was performed by the CFD-FASTRAN search code, using the k-w SST model as the turbulence model. The calculation is performed by solving the Navier-Stokes equations of twodimensional compressible turbulent flow. It is based on the study of the fluidic vectorization phenomenon of the thrust of a double-injection convergent-divergent supersonic conical nozzle. The study is based on the effect of the ratio of NPR pressures with SPR = 1 on the overall structure of shock waves. The calculation is highlighting the behavior of a flow that has not neglected. In particular, the appearance of the separation zone formed by the fluid jet and the deflection of the main jet cause separation shocks
Article
Keywords: Shock wave, fluidic vectorization, boundary layer, returns flow, Navier-Stokes equations.